2002
DOI: 10.1054/brst.2002.0464
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous stereotactic en bloc excision of nonpalpable breast carcinoma: a step in the direction of supraconservative surgery

Abstract: SUMMARYRecently, the advanced breast biopsy instrumentation (ABBI) system has been introduced as an alternative to conventional breast biopsy techniques. This study was prospectively conducted to evaluate the potential of the ABBI method in locoregional management of a consecutive series of patients with nonpalpable mammographically detected breast carcinomas. Sixty-one consecutive patients underwent an ABBI procedure as a first step before possible surgery for nonpalpable breast lesions that would in any case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The lesion cannot always be removed successfully1, and the biopsy margins are often affected2. However, with growing experience and improving case selection, these drawbacks have largely been overcome3, 4. The most suitable lesions are either nodules or very well circumscribed clusters of microcalcification less than 15 mm in diameter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lesion cannot always be removed successfully1, and the biopsy margins are often affected2. However, with growing experience and improving case selection, these drawbacks have largely been overcome3, 4. The most suitable lesions are either nodules or very well circumscribed clusters of microcalcification less than 15 mm in diameter.…”
Section: Discussionmentioning
confidence: 99%
“…The question addressed in this report has been examined before4, 5. Lifrange et al 4 found that involvement of breast tissue around a lesion was inversely related to tumour size4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation